The Ectopic Expression of CaRop1 Modulates the Response of Tobacco Plants to Ralstonia solanacearum and Aphids - Qiu, Ailian; Liu, Zhiqin; Li, Jiazhi; Chen, Yanshen; Guan, Deyi; He, Shuilin (Frontiers in Plant Science, 2016)
In plants, Rho-related GTPases (Rops) are versatile molecular switches that regulate various biological processes, although their exact roles are not fully understood. Herein, we provide evidence that the ectopic expression of a Rop derived from Capsicum annuum, designated CaRop1, in tobacco plants modulates the response of these plants to Ralstonia solanacearum or aphid attack. The deduced amino acid sequence of CaRop1 harbors a conserved Rho domain and is highly homologous to Rops of other plant species. Transient expression of a CaRop1-GFP fusion protein in Nicotiana benthamiana leaf epidermal cells revealed localization of the GFP signal to the plasma membrane, cytoplasm, and nucleus. Overexpression (OE) of the wild-type CaRop1 or its dominant-negative mutant (DN-CaRop1) conferred substantial resistance to R. solanacearum infection and aphid attack, and this effect was accompanied by enhanced transcriptional expression of the hypersensitive-reaction marker gene HSR201; the jasmonic-acid (JA)-responsive PR1b and LOX1; the insect resistance-associated NtPI-I, NtPI-II, and NtTPI; the ethylene (ET) production-associated NtACS1; and NPK1, a mitogen-activated protein kinase kinase kinase (MAPKKK) that interferes with N-, Bs2-, and Rx-mediated disease resistance. In contrast, OE of the constitutively active mutant of CaRop1(CA-CaRop1) enhanced susceptibility of the transgenic tobacco plants to R. solanacearum infection and aphid attack and downregulated or sustained the expression of HSR201, PR1b, NPK1, NtACS1, NtPI-I, NtPI-II and NtTPI. These results collectively suggest that CaRop1 acts as a signaling switch in the crosstalk between Solanaceaes’s response to R. solanacearum infection and aphid attack possibly via JA/ET-mediated signaling machinery.